Over 75 recipes, from jams to jammy dodgers and marmalades to muffins - Doherty, Fraser (Ebury Press : [distributor] TBS The Book Service Ltd, 2010)
Contains recipes for jams, marmalades, chutneys and jellies. This book offers ideas for spreads, such as Banana and Rum Curd, Dulce de Leche and Chilli Jam. It includes over 25 ideas for how to turn your creations into puddings, from Bakewell Tart and Orange and Passion Fruit Trifle to Banoffee Cupcakes and Strawberry and White Chocolate Mousse